Proactive Monitoring and Compliance with International Financial Reporting Standard in Nigeria - Bagudo, Muhammad Mustapha; Manaf, Kamarul Bahrain Bin Abdul; Ishak, Rokiah Bt. (International Journal of Economics and Financial Issues, 2016)
The study examines how proactive monitoring by regulatory authorities and external auditors affect compliance with International Financial Reporting Standard (IFRS) in Nigeria. Data is hand collected from 154 companies that mandatorily adopted IFRS in the year 2012. The study uses the unweighted index in determining the extent of compliance with the disclosure requirements of 10 standards and uses multiple regressions in examining how proactive monitoring affects compliance with IFRS. The results show that the overall level of compliance is 61% and the regulatory bodies under insurance companies and firms audited by Big-4 auditors significantly and positively affect the level of compliance with IFRS disclosures. The study recommends an increase in vigilant in monitoring compliance with IFRS by the regulatory bodies supervising non-financial firms and by local audit firms to improve compliance. Keywords: Proactive monitoring; compliance with IFRS; Nigeria. JEL Classifications: C31; M41